Avaliação microbiológica, físico-química e anatomopatológica de frangos de corte com caquexia - Nery, Leandro Cayres (2016)
The present work aims to perform a microbiological, physicochemical and histopathological characterization of carcasses of poultry with cachexia which, according to the health law in force, have to be fully condemned. Mixed batches of Cobb broiler chickens of minimum age of 43 days and maximum age of 48 days were collected from two integration companies after being identified as cachectic in the pre-inspection area by the Federal Inspection Service, with reduced size and weight, reduced muscular mass mainly characterized by low coverage of breast muscle and showing of the breastbone. Those were macroscopically tested at the Final Inspection Department so only chickens without any apparent sign of systemic infectious impairment could be used in the work, also assessing offal components. Cachectic carcasses used in the study presented average weight of 0.6213kg (σ = 0.1378kg). There was no significant microbiological difference between companies and the results complied with the law in force. In physicochemical analyses, there was a significant difference in four out of six analyses performed (lipids, protein, humidity and volatiles, and pH) when compared to healthy carcasses coming from the same batch (average weight: 1.6779kg; σ = 0.2135kg); there was no significant difference to the analyses of mineral fixed residues and all carcasses tested negative to sulphidric gas reaction. Histopathologically, to the optical microscopy, in offal samples (heart, liver, kidneys, and pancreas) and muscles (Pectoralis major) of 20 cachectic chickens assessed, none presented changes in offal components. In relation to the muscles, 65% of the samples did not present any lesion, 20% presented mild degree and 15% moderate degree of myodegeneration. The results showed the importance of further investigating the characteristics involving the reasons for condemnation due to cachexia, thus opening the discussion about the feasibility of different destinations to them, allowing for better use and preventing economic losses.